ANALYZE THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, MOTIVATION AND PARTICIPATION IN BUDGETING ON MANAGERIAL PERFORMANCE WITH WORK SATISFACTION AS INTERVENING VARIABLE AT POLITEKNIK UNGGUL LP3M MEDAN - Nasir, Miftah Faridh (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the influence of organizational commitment, motivation, and participation in budgeting on managerial performance with work satisfaction as intervening variable at Politeknik Unggul LP3M, Medan. The research used comparative causal which indicated the causal correlation among variables. The population was 115 respondents, and 100 of them were used as the samples, taken by using total sampling technique. The data   were gathered by using Structural Equation Model (SEM) with PLS approach. The result of the research showed that organizational commitment and work satisfaction had positive and significant influence on managerial performance, while motivation and participation in budgeting did not have any significant influence managerial performance. Organizational commitment, motivation, and participation in budgeting had positive and significant influence on work satisfaction. Work Satisfaction could only mediate the correlation between organizational commitment and managerial performance but it could not mediate the correlation of motivation and participation of budgeting with managerial performance.